Human Metapneumovirus Infection Induces Significant Changes in Small Noncoding RNA Expression in Airway Epithelial Cells - Junfang Deng; Ryan N Ptashkin; Qingrong Wang; Guangliang Liu; Guanping Zhang; Inhan Lee; Yong Sun Lee; Xiaoyong Bao (Elsevier, 2014)
Small noncoding RNAs (sncRNAs), such as microRNAs (miRNA), virus-derived sncRNAs, and more recently identified tRNA-derived RNA fragments, are critical to posttranscriptional control of genes. Upon viral infection, host cells alter their sncRNA expression as a defense mechanism, while viruses can circumvent host defenses and promote their own propagation by affecting host cellular sncRNA expression or by expressing viral sncRNAs. Therefore, characterizing sncRNA profiles in response to viral infection is an important tool for understanding host-virus interaction, and for antiviral strategy development. Human metapneumovirus (hMPV), a recently identified pathogen, is a major cause of lower respiratory tract infections in infants and children. To investigate whether sncRNAs play a role in hMPV infection, we analyzed the changes in sncRNA profiles of airway epithelial cells in response to hMPV infection using ultrahigh-throughput sequencing. Of the cloned sncRNAs, miRNA was dominant in A549 cells, with the percentage of miRNA increasing in a time-dependent manner after the infection. In addition, several hMPV-derived sncRNAs and corresponding ribonucleases for their biogenesis were identified. hMPV M2-2 protein was revealed to be a key viral protein regulating miRNA expression. In summary, this study revealed several novel aspects of hMPV-mediated sncRNA expression, providing a new perspective on hMPV-host interactions.